Selective Small Molecule Inhibition of Poly(ADP-Ribose) Glycohydrolase (PARG) - Kristin E. Finch; Claire E. Knezevic; Amanda C. Nottbohm; Kathryn C. Partlow; Paul J. Hergenrother (2012)
The poly(ADP-ribose) (PAR) post-translational modification is essential for diverse cellular functions, including regulation of transcription, response to DNA damage, and mitosis. Cellular PAR is predominantly synthesized by the enzyme poly(ADP-ribose) polymerase-1 (PARP-1). PARP-1 is a critical node in the DNA damage response pathway, and multiple potent PARP-1 inhibitors have been described, some of which show considerable promise in the clinic for the treatment of certain cancers. Cellular PAR is efficiently degraded by poly(ADP-ribose) glycohydrolase (PARG), an enzyme for which no potent, readily accessible, and specific inhibitors exist. Herein we report the discovery of small molecules that effectively inhibit PARG in vitro and in cellular lysates. These potent PARG inhibitors can be produced in two chemical steps from commercial starting materials and have complete specificity for PARG over the other known PAR glycohydrolase (ADP-ribosylhydrolase 3, ARH3) and over PARP-1 and thus will be useful tools for studying the biochemistry of PAR signaling.